The Degree to Which Arabic Language ‎Female Teachers in the Sultanate of Oman ‎Possess 21st Century Skills as Viewed by ‎School Principals and Educational ‎Supervisors - Al-Awadiah ‎, Najat; Al-Monzeryah, Rayya (Jordan Journal of Educational Sciences, 2024)
This study aimed to identify the degree of Arabic language teachers' possession of twenty-first century skills from the point of view of female school principals and male educational supervisors in the Sultanate of Oman. The study sample consisted of 68 female principals and 14 male and female supervisors. The study employed a descriptive design and utilized a questionnaire with 30 items categorized into 3 domains and 7 main skills: critical thinking, problem solving, communication culture, information and media literacy, collaboration, teamwork and leadership, innovation and creativity, technology culture, information and communication technology, professional and self-directed learning, and cross-cultural understanding. Subsequently, it was implemented in the study sample.. The study's results indicated that school principals found Arabic language teachers to have a significant level of twenty-first century skills, with an average score of 3.56. On the other hand, educational supervisors rated the possession of these skills by Arabic language teachers as moderate, with an average score of 3.00. The study recommended enhancing the training of female teachers in twenty-first century skills during their service, incorporating these skills into school curricula and teacher guides, and integrating technological applications and communication networks into educational settings at schools and universities